On the interplay between intermetallic controlled growth and hot tearing susceptibility in Al-to-steel welding with additional interlayers. (15th October 2019) - Jimenez-Mena, N.; Simar, A.; Jacques, P.J.
Abstract: The brittle behaviour of Fe/Al intermetallic compounds formed during dissimilar Al-to-steel welding is a major drawback for the mechanical integrity of the joint, particularly for thick intermetallic layers. In order to improve the toughness of the weld, the control of the thickness and the nature of the intermetallic layer have been investigated owing to the addition of an electroplated nickel or cobalt interlayer prior to welding by the novel Friction Melt Bonding (FMB) process. The FMB joining of DP600 steel and AA1050 is achieved by the wetting and reaction of liquid aluminium to the solid steel surface and subsequent solidification. Nevertheless, hot tears, also appear owing to the dissolution of the interlayer in the liquid aluminium. The dissolution and diffusion of the interlayer has been analysed and modelled using the second Fick's diffusion law when imposing a kinetic dissolution behaviour at the interface. The risk of hot tearing was assessed using the Scheil-Gulliver model to calculate the solidification path and a composition-based hot tearing criterion. As a result of the dissolution of the interlayer, the composition of the molten pool evolves, which leads to changes in the nature, morphology and thickness of the reaction interlayer. Graphical abstract: Unlabelled Image Highlights: The thickness of the intemetallic layer in Al-to-steel welding is greatly reduced with the use of Co and Ni interlayers Dissolution of the interlayer in liquid aluminium changes the behaviour of the latter and bring the formation of hot tears A model for interlayer dissolution in liquid aluminium combined to a hot tearing criterion predicts the experimental results